The story of SF5-substituted pyridines. (3rd July 2019) - Cui, Benqiang; Shibata, Norio
Abstract: Synthetic approaches to pentafluoro-λ 6 -sulfanylated pyridines, including meta- ( m- ) and para - ( p- ) pentafluoro-λ 6 -sulfanyl-substituted pyridines and ortho- ( o- )-pentafluoro-λ 6 -sulfanyl-substituted pyridines containing strong electron-withdrawing substituents, are summarized in this review. GRAPHICAL ABSTRACT: UF0001